Case of stanford type B aortic dissection treated with thoracic endovascular aortic repair and retrograde abdominal artery embolization - Yusuke Kato; Wataru Tatsuishi; Yasunobu Konishi; Kei Shibuya; Kazuki Tamura; Naoki Konno; Tomonobu Abe (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Introduction: Patients with Stanford type B aortic dissection with a residual false lumen have an unfavorable long-term prognosis. Endovascular repair is the most common invasive treatment.1 Endovascular repair in aortic dissection has a high complication frequency, and it is important to prevent such complications. This case highlights a Stanford B acute aortic dissection with a high possibility of Type II endoleak from the celiac artery. In order to prevent endoleak, it was necessary to embolize the celiac artery. However, since the left gastric artery branched off from the aorta near the opening of the celiac artery, there was a high possibility of bifurcation ischemia with celiac artery embolization. Therefore, we performed a difficult retrograde celiac artery embolization technique via the superior mesenteric artery. Case report: A 70-year-old woman with a history of hypertension, hyperlipidemia, and smoking, presented with complicated pseudoaneurysmal Stanford type B aortic dissection. She was treated with thoracic endovascular aortic repair and retrograde embolization of the celiac artery via the superior mesenteric artery, which prevented a type II endoleak from the celiac artery without compromising its branches. Because we were able to preserve the left gastric artery, which branched off from the celiac artery close to the aortic orifice, left hepatic arterial flow was maintained. Discussion: We embolized the celiac artery using a retrograde approach from the superior mesenteric artery to the celiac artery. The advantages of this approach are that it prevents distal migration of the coil due to progressive flow and the retrograde build-up from the false lumen shortens the embolization distance in the celiac artery compared with that in the progressive approach, wherein the catheter tip is placed at the origin of the celiac artery. Conclusion: Thoracic endovascular repair with retrograde embolization of the celiac artery for Stanford type B aortic dissection is an effective technique to avoid embolization of the branches of the celiac artery.